PHYSICAL EDUCATION TEACHERS AND THE INDEPENDENT CURRICULUM: A STUDY OF PERCEPTION - Gunawan; Humaedi; Saparia, Andi (STKIP Citra Bakti, 2025)
This research aims to identify physical education teachers' perceptions of the independent curriculum. Quantitative descriptives were used in this research with a cross-sectional study design. The population is 56 physical education teachers spread across the city of Palu. The analysis technique uses descriptive statistics. The results show that the majority of respondents provided very positive support for the independent curriculum, with many feelings interested and finding it useful. However, there are still some respondents who doubt or disagree, indicating the need for more effective communication and deeper understanding to ensure broad and effective acceptance at all levels of education. The majority of respondents showed a strong interest in following developments in the independent curriculum, although there were doubts that needed to be overcome. Challenges in getting support were also apparent, with some respondents preferring other curricula and viewing the independent curriculum as a temporary policy. This emphasizes the importance of effective communication and transparency from the government. In particular, research shows that respondents have diverse views regarding the implementation of the independent curriculum in physical education.